2018
DOI: 10.3390/nano8100750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al3+ Substitution on Structural and Magnetic Behavior of CoFe2O4 Ferrite Nanomaterials

Abstract: A sol-gel autocombustion method was used to synthesize Al3+ ion-substituted cobalt ferrite CoAlxFe2−xO4 (x = 0–1.5). According to X-ray diffraction analysis (XRD), cobalt ferrite was in a single cubic phase after being calcined at 1000 °C for 3 h. Moreover, the lattice constant decreased with increase in aluminum substituents. When the sample was analyzed by Scanning Electron Microscopy (SEM), we found that uniformly sized, well-crystallized grains were distributed in the sample. Furthermore, we confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The SAED patterns are compatible with the noncrystalline structure reported in the literature. 37–39 The Debye circles are more intense for uncoated than the coated nanoparticles because of the higher degree of dispersion in the coated particles in a region. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAED patterns are compatible with the noncrystalline structure reported in the literature. 37–39 The Debye circles are more intense for uncoated than the coated nanoparticles because of the higher degree of dispersion in the coated particles in a region. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The goodness of fit χ 2 varies between 0.641 to 3.112, which is within acceptable limits. 38,39 Manova et al 40 showed that the Fe 3+ sub-spectrum with a larger isomer shift represents octahedral B-sites while the Fe 3+ sub-spectrum with a lower isomer shift represents tetrahedral A-sites. The covalent bond of the A-sites is more potent than that of the B-sites because of the larger internuclear separation of ferric and oxygen ions at the B-site than the A-site, and the orbital overlap is smaller at the B-site than the A-site.…”
Section: Resultsmentioning
confidence: 99%
“…Various parameters governed the coercivity, like grain size, magnetic particle morphology, magnetocrystalline anisotropy, strains and exchange coupling between the collinear spins in the core, and the canted spins on the surface [34,35]. The improvement in coercive field can be principally attributed to the increase of magnetocrystalline anisotropy [44,45]. Equation (1) describes the proportionality between the coercivity H c and magnetic anisotropy constant K a [44].…”
Section: Resultsmentioning
confidence: 99%
“…The improvement in coercive field can be principally attributed to the increase of magnetocrystalline anisotropy [44,45]. Equation (1) describes the proportionality between the coercivity H c and magnetic anisotropy constant K a [44]. Hc2KaμoMs where μo is the permeability constant.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic properties get altered by intrinsic as well extrinsic prop- erties and it has been found that also, sintering temperature can tailor magnetic variations [51] anisotropy constant = H c × M s 0.96 (7) Bohr magnetization (𝜇B) = M × M s 5585 (8) The anisotropy constant decreases with increase in temperature might be due to the chance of presence of Al ion in tetrahedral site is more at higher temperature which further decrease the spin orbital interaction between ions of iron. [52,53] Further in order to check the microwave operation frequency at which these sintered samples can be operated, which is depend upon saturation magnetization of nano ferrites and can be calculated using Equation ( 9) [54,55] and value is given in Table 3 𝜔 m = 8𝜋 2 𝛾M s (9) where 𝜔 m is the microwave operating frequency, 𝛾 is the gyromagnetic ratio of ferrites in microwave region and is equal to 2.8 MHz/O e , and M s is the saturation magnetization. The value 𝜔 m for all sintered samples lie in the ultrahigh-frequency range.…”
Section: Vsmmentioning
confidence: 99%